Managing behavioural and psychological symptoms in community dwelling older people with dementia: 1. A systematic review of the effectiveness of interventions. (November 2019) - Trivedi, Daksha P; Braun, Andreas; Dickinson, Angela; Gage, Heather; Hamilton, Laura; Goodman, Claire; Ashaye, Kunle; Iliffe, Steve; Manthorpe, Jill
Background: Two-thirds of people living with dementia live at home in the UK and many experience distressing behavioural and psychological symptoms. This systematic review evaluates the effectiveness of non-pharmacological interventions for behavioural and psychological symptoms among community-dwelling people living with dementia. Methods: This two-stage review undertook an initial mapping of the literature followed by a systematic review of relevant randomised controlled trials. We searched electronic databases for pertinent studies reporting outcomes from interventions from January 2000 to March 2015 and updated searches in October 2016. We included studies that considered behavioural and psychological symptom management for older people living with dementia who live at home and excluded studies conducted in long-term care settings. This paper presents findings from a narrative synthesis of 48 randomised controlled trials evaluating interventions for people living with dementia alone, family carers alone and patient-carer dyads. Results: We retrieved 17, 871 de-duplicated records and screened them for potential inclusion. Evidence from 48 randomised controlled trials suggests that family carer training and educational programmes that target problem behaviours and potential triggers can improve outcomes. Nurses and occupational therapists appear to help people with dementia with behavioural and psychological symptoms, but professional comparisons are lacking and there is no shared language about or understanding of behavioural and psychological symptoms amongst professionals, or between professionals and family carers. Conclusions: Future research should focus on the effectiveness of components of multi-faceted programmes and their cost effectiveness and include qualitative data to better target interventions for behavioural and psychological symptoms. It is important to consider family carer readiness to use non-pharmacological strategies and to develop a shared language about the inherent needs and communications of behavioural and psychological symptoms.